2014
DOI: 10.1185/03007995.2014.968704
|View full text |Cite
|
Sign up to set email alerts
|

Drug treatment patterns for the management of men with lower urinary tract symptoms associated with benign prostatic hyperplasia who have both storage and voiding symptoms: a study using the health improvement network UK primary care data

Abstract: Background: Real-world data on the pharmacological management of men who have lower urinary tract symptoms (LUTS) associated with benign prostatic hyperplasia (BPH) are limited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 17 publications
3
33
1
Order By: Relevance
“…Previously reported data from a large, retrospective observational cohort study of 8694 men with LUTS/BPH in the UK showed that fewer patients discontinued (43.0% vs. [mean] 53.0%) or switched treatment (15.3% vs. [mean] 22.0%) from solifenacin compared with most other antimuscarinics, and persisted on-treatment for longer (median duration, 90 days vs. [range] 30–116 days) [16]. These findings are supported by further real-world data in patients with OAB, suggesting that solifenacin provides greater treatment persistence compared with other antimuscarinics (mean persistence 187 vs. 77–157 days; persistence at 12 months, 35% vs. 14%–28%) [24].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously reported data from a large, retrospective observational cohort study of 8694 men with LUTS/BPH in the UK showed that fewer patients discontinued (43.0% vs. [mean] 53.0%) or switched treatment (15.3% vs. [mean] 22.0%) from solifenacin compared with most other antimuscarinics, and persisted on-treatment for longer (median duration, 90 days vs. [range] 30–116 days) [16]. These findings are supported by further real-world data in patients with OAB, suggesting that solifenacin provides greater treatment persistence compared with other antimuscarinics (mean persistence 187 vs. 77–157 days; persistence at 12 months, 35% vs. 14%–28%) [24].…”
Section: Discussionmentioning
confidence: 99%
“…However, the pattern of prescriptions across the antimuscarinics was more balanced in these studies, suggesting that the proportion of patients prescribed with solifenacin in the current study (74.4%) may be specific to the Netherlands. Regarding α-blockers, tamsulosin is reported to be the most commonly used for LUTS/BPH [16], but it should also be noted that the impact of individual α-blockers used in combination on persistence, adherence or switching were not assessed in the same way as antimuscarinics in this study; this could perhaps be evaluated in further studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Historically, oral antimuscarinic agents have been the mainstay of OAB therapy, although the associated side‐effects (including dry mouth and constipation) further affect quality of life and adversely affect treatment adherence . Treatment persistence of OAB medication is lower than for any other chronic disease therapy, with a number of studies demonstrating poor treatment persistence with antimuscarinics . As such, OAB treatments with alternative mechanisms of action and improved tolerability are desirable.…”
Section: Introductionmentioning
confidence: 99%
“…The most commonly prescribed α₁-blocker was tamsulosin (81.8%); and most frequent antimuscarinics was Tolterodine (41.0%). 6 The efficacies of all drugs were assessed on the basis of mean change difference in IPSS score, Qmax, and Qavg.…”
Section: Discussionmentioning
confidence: 99%